Concert Hall, Museum, Cinema, and Theater Attendance: What Difference Do Audience Motivations and Demographics Make?. (January 2022) - Manolika, Maria; Baltzis, Alexandros
Given the ubiquity of art in almost all human societies, why is it that participation in the arts is so diverse? To address this question, the present study examined demographic and motivational variables as predictors of arts attendance in a sample of 480 participants, and whether any significant differences appear among attendees at different venues. The ordinal logistic regression identified income, entertainment, and art interest as predictors of arts attendance, with income leading to greater attendance at several art forms. Subsequent analyses also unveiled significant differences in demographic and behavioral characteristics among concert hall attendees, museum visitors, cinema goers, and theater audiences. Taken together, these findings illustrate that audience behavior is selective and incited by conscious awareness of a person's unique needs. From an applied perspective, adequate knowledge of human functioning will enable arts managers to attract new audiences, without neglecting their responsibility towards art, culture, and education.